Metal Catalyzed Reductive C-C Bond Formation [electronic resource] : A Departure from Preformed Organometallic Reagents - Krische, Michael J.; SpringerLink (Online service) (Berlin Heidelberg : Springer-Verlag GmbH., 2007)
PSZJBL